2017
DOI: 10.22159/ajpcr.2017.v10i5.17436
|View full text |Cite
|
Sign up to set email alerts
|

Migraine: A Possible Cause for Cognitive Decline

Abstract: Objectives: Migraine is the second most common type of headache and seventh most disabling disease worldwide. In general, obesity is often related to headache disorders in several clinical and epidemiologic studies. Obese migraine patients may have an increased attack frequency due to the increase in inflammatory response. Cognitive decline is present in several migraine patients. However, some researchers differ. Body mass index (BMI) is also seen to have a role in migraine. This study has been done (i) to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Poormina et al. (2017) also found that mean time needed to complete the Stroop test was significantly higher for migraineurs ( M = 132.17, SD = 7.027 s) compared to controls ( M = 106.40, SD = 15.87 s, p < 0.001), thus suggesting inter‐ictal attention and processing speed impairments in the migraine population. This attentional deficit may further worsen as a migraine cycle progresses.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Poormina et al. (2017) also found that mean time needed to complete the Stroop test was significantly higher for migraineurs ( M = 132.17, SD = 7.027 s) compared to controls ( M = 106.40, SD = 15.87 s, p < 0.001), thus suggesting inter‐ictal attention and processing speed impairments in the migraine population. This attentional deficit may further worsen as a migraine cycle progresses.…”
Section: Resultsmentioning
confidence: 96%
“…With regards to attention, studies show quite a consistent pattern of attention and information processing speed deficits in migraineurs (Agessi et al., 2014; Ferreira et al., 2018; Gil‐Gouveia et al., 2015b; Martins et al., 2012; Mickleborough et al., 2013; Poormina et al., 2017), with some reporting a specific poorer performance in female patients (Guo et al., 2019). Yannick et al.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations